Investor Reaction to the Ambiguity and Mix of Positive and Negative Argumentation in Favorable Analyst Reports - Winchel, Jennifer (Contemporary Accounting Research, 2015)
Abstract This study experimentally tests the hypothesis that investor reaction to favorable investment ratings is influenced by attributes of analysts’ supporting arguments. Specifically, I argue that argument ambiguity and the mix of positive and negative argumentation interact to influence how investors process and, in turn, react to information contained in analysts’ arguments. When positive arguments are unambiguous, I predict and find that investors react to the content of the arguments because they perceive the arguments provide sufficient support for the rating. In this case, investors react more favorably when the report includes strictly positive argumentation (i.e., one‐sided argumentation) than when it includes a mix of positive and negative argumentation (i.e., two‐sided argumentation). In contrast, when positive arguments are ambiguous, two‐sided argumentation acts as a credibility cue and leads to a higher likelihood of investment than one‐sided argumentation. These results provide important insights about the conditions under which investors react to justifications in favorable analyst reports and shed light on how analysts can credibly convey favorable information.